2023
DOI: 10.3389/fimmu.2023.1156762
|View full text |Cite
|
Sign up to set email alerts
|

Bacteroides fragilis strain ZY-312 facilitates colonic mucosa regeneration in colitis via motivating STAT3 signaling pathway induced by IL-22 from ILC3 secretion

Abstract: IntroductionProbiotics play critical roles in relieving inflammatory bowel disease (IBD). However, the underlying mechanism of Bacteroides fragilis strain ZY-312 (B. fragilis) for colonic mucosa regeneration in IBD remains unclear.MethodsThe weight loss, disease activity index (DAI), colon length, and histopathology-associated index (HAI) were evaluated the therapeutic effects of B. fragilis in a DSS-induced colitis mouse model. Colonic mucosa proliferation and apoptosis level, and mucus density were detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…B. fragilis , a pivotal inhabitant of the human gastrointestinal tract, plays a dual role in health, acting both as a beneficial probiotic and a potential opportunistic pathogen [ 11 ]. Early research has revealed that B. fragilis plays a role in modulating the gut microbiome by interfering with the growth or translocation of other microbes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…B. fragilis , a pivotal inhabitant of the human gastrointestinal tract, plays a dual role in health, acting both as a beneficial probiotic and a potential opportunistic pathogen [ 11 ]. Early research has revealed that B. fragilis plays a role in modulating the gut microbiome by interfering with the growth or translocation of other microbes.…”
Section: Discussionmentioning
confidence: 99%
“…For immune regulation, studies note that B. fragilis ’s Polysaccharide A (PSA) is crucial and may protect against diseases like bowel disease [ 11 , 31 ]. B. fragilis administration in animal models leads to the binding of PSA with B cells, crucial for inducing regulatory CD4+ and CD8+ T cells that secrete IL-10, thereby controlling innate inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intermediate stages of NK development are also thought to differentiate from this progenitor, at least in secondary lymphoid tissues, such as tonsils and lymph nodes (20). ILC differentiation further leads to the early tonsil progenitor cells (EToP), with two distinct phenotypes, EToP1 (Lin − CD34 + CD10 + KIT − ) or EToP2 (Lin − CD34 + CD10 + KIT + ) (21,22). EToP2 can be divided into two groups based on ST2 (IL-33R, IL1r1) expression and on their ability to form ILC (21).…”
mentioning
confidence: 99%